A life together, a life apart : a history of relations between Europeans and Aborigines - Attwood, Bain. (Carlton, Vic. : Melbourne University Press, 1994)
"[T]he testimony of Winifred Burrage, Alan Burrage and Elsie Stokie, whose parents, Charles and Elsie Burrage, managed or taught on Aboriginal reserves in New South Wales in the period between World War I and World War II"--P. xiii.
Bain Attwood (New Zealand author)
Includes bibliographical references (p. 220-232).
Keywords: Burrage, Charles, -- 1879-1959.; Burrage, Elsie, -- 1892-1969.; Burrage, Winifred, -- 1914-1993 -- Childhood; Burrage, Alan, -- 1916- -- Childhood; Stokie, Elsie, -- 1918- -- Childhood; Aboriginal Australians -- New South Wales -- Treatment; Aboriginal Australians -- New South Wales -- Social conditions